Strategi Sekolah dalam Meningkatkan Daya Saing di Era Kompetisi Pendidikan: Tinjauan dari Perspektif Pilihan Rasional Studi Kasus di SMK Mulia Bakti Purwokerto - Mahfud; Hanif, Muhammad (At-Tadris: Journal of Islamic Education, 2024)
This study examines the strategies implemented by SMK Mulia Bakti Purwokerto in increasing competitiveness amidst the tight competition in education, especially in the era of globalization that demands the quality of graduates who are ready to work and highly competitive. Based on the rational choice perspective, this study focuses on how schools make strategic decisions that can improve the quality of learning and attract prospective students. This study shows that SMK Mulia Bakti implements various innovations, such as industry-based curriculum, one-machine-one-student system, teaching factory, and learning block system to prepare students with practical skills relevant to industry needs. In addition, 70% of learning time is allocated for practicums, which increases students' work readiness. Other important findings are the increase in the number of students by 200% in the last two years, as well as the absorption rate of graduates into the workforce which reached more than 80% in the first six months after graduation. This approach has also proven successful in attracting more students to enroll in this school, indicating that the quality of practice-based education can strengthen the attractiveness of SMK in the eyes of the public. This study provides recommendations to improve cooperation with the business world and expand the application of industry-based curriculum in other vocational schools to strengthen the competitiveness of vocational education in Indonesia.